„Negatyw świata”. Inspiracje techniką graficzną jako źródło refleksji metaliterackiej – na przykładzie wiersza Ewy Lipskiej Albatros i grawer - Szewczyk-Haake, Katarzyna (Przestrzenie Teorii, 2022)
The paper presents an analysis of Ewa Lipska’s poem Albatros i grawer [‘The Albatross and the Engraver’], which is a rare example of evoking a work of graphic art in a poem. The metaphors used in the text, exploiting the field of meaning related to graphics, become the basis for metaliterary reflection. Important interpretative contexts indicated in the article are, on one hand, the history of graphic art and its technical arcana, and on the other, the poem The Albatross by Charles Baudelaire, alluded to in the poem and, by the same token, modernist ideas about the art and the artist. The poem’s consideration of the problem of ‘a negative’ and ‘an imprint’ leads to questions about the relationship between art and reality, a relationship which, radically transformed in the modern era, demands an ethical evaluation, just as the poem suggests.